Prove that its right.
asked Jul 20, 2012 in Trigonometry Answers by anonymous

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

1 Answer

(cscA)(sin2A) - secA = (cos2A)(secA)

LHS=(cscA)(sin2A) - secA

    =(1/sinA)(2sinAcosA)-secA

  =2cosA-secA

=2cosAsecA/secA  -secA

=2 cos^2(A)secA-secA

=(2 cos^2(A) - 1)secA

=(cos2A)(secA)=RHS

 

 

 

answered Jul 20, 2012 by soudhamini Level 5 User (14,740 points)
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
77,101 questions
80,524 answers
1,617 comments
58,772 users